Numerical analysis of free vibration frequencies of pentagonal plates - Grigorenko, A.Ya.; Borysenko, M.Yu.; Sperkach, S.О.; Bezuglaya, А.D.; Mikhrin, E.O (Reports of the National Academy of Sciences of Ukraine, 2022)
Free vibrations of the isotropic pentagonal plates of the different thicknesses with the free edges are considered based on two different approaches. The approach Rayleigh—Ritz method has been extended to the calculation of the frequencies of free vibrations of pentagonal plates. Frequencies and forms of free vibrations of the plates of this class are calculated by the finite element method (FEM). The frequencies calculated were compared and the accuracy of the calculations by the two methods was established. The modes of the vibrations obtained based on the FEM are compared with the modes of vibrations obtained numerically and experimentally by other authors.